Viable SARS-CoV-2 Omicron sub-variants isolated from autopsy tissues - Maffia-Bizzozero, Santiago; Cevallos, Cintia; Lenicov, Federico Remes; Freiberger, Rosa Nicole; Lopez, Cinthya Alicia Marcela; Guano Toaquiza, Alex; Sviercz, Franco; Jarmoluk, Patricio; Bustos, Cristina; D’Addario, Adriana Claudia; Quarleri, Jorge; Delpino, M. Victoria (Frontiers in Microbiology, 2023)
Pulmonary and extrapulmonary manifestations have been described after infection with SARS-CoV-2, the causative agent of coronavirus disease 2019 (COVID-19). The virus is known to persist in multiple organs due to its tropism for several tissues. However, previous reports were unable to provide definitive information about whether the virus is viable and transmissible. It has been hypothesized that the persisting reservoirs of SARS-CoV-2 in tissues could be one of the multiple potentially overlapping causes of long COVID. In the present study, we investigated autopsy materials obtained from 21 cadaveric donors with documented first infection or reinfection at the time of death. Among the cases, there were COVID-19 vaccine recipients including different formulations and doses received. The aim was to find the presence of SARS-CoV-2 in the lungs, heart, liver, kidneys, and intestines. We used two technical approaches: the detection and quantification of viral genomic RNA using RT-qPCR, and virus infectivity using permissive in vitro Vero E6 culture. All tissues analyzed showed the presence of SARS-CoV-2 genomic RNA, but at dissimilar levels ranging from 1.01x102 copies/mL to 1.14x108 copies/mL, even among those cases who had been COVID-19 vaccinated. Importantly, different amounts of replication-competent virus were detected in the culture media from the studied tissues. The highest viral load levels were measured in the lung (~1.4x106 copies/mL) and heart (~1.9x106 copies/mL) samples. Additionally, based on partial Spike gene sequences, SARS-CoV-2 characterization revealed the presence of multiple Omicron sub-variants exhibiting a high level of nucleotide and amino acid identity among them. These findings highlight that SARS-CoV-2 can spread to multiple tissue locations such as the lungs, heart, liver, kidneys, and intestines, both after primary infection and after reinfections with the Omicron variant, contributing to extending knowledge about the pathogenesis of acute infection, and understand the sequelae clinical manifestations that are observed during post-acute COVID.